Emotional regulation behaviours and later behavioural adjustment in young children - Ong, Claire Tze Yee (Nanyang Technological University, 2024)
Emotional regulation is the ability of an individual to modulate an emotion or a set of emotions (American Psychological Association, n.d.). Behavioural adjustment includes externalising and internalising behaviour (Bornstein et al., 2010). Current research has demonstrated the relationship between emotional regulation and behavioural adjustment in young children. This study sought to explore this relationship in a younger age group of children than what is present in the current literature. The main research question was: How do emotional regulation skills predict later behavioural adjustment? Participants (N = 43, 43.18% male) were part of a longitudinal study, BE POSITIVE. Emotional regulation skills were observed at the 9-11 months time point in the LAB-TAB robot task, and behavioural adjustment was reported by parents using the Strengths and Difficulties Questionnaire (SDQ 2-4; Goodman, 1997). Using correlations and regression analyses, this study investigated the predictive strengths of emotional regulation skills on behavioural adjustment. The results demonstrated that reaching stimulus and vocalising to caregiver both significantly predicted lower externalising behaviour. Overall, our study adds to the current research on emotional regulation skills as predictors of behavioural adjustment, and there is a need to place more emphasis on encouraging social communication in young children, as well as developing attentional control.